2010
DOI: 10.1007/s10519-010-9370-0
|View full text |Cite
|
Sign up to set email alerts
|

Across-Line SNP Association Study for Direct and Associative Effects on Feather Damage in Laying Hens

Abstract: An association study between SNP markers and feather condition score on the back, rump and belly of laying hens was performed. Feather condition score is a measure of feather damage, which has been shown to be closely related to feather pecking behaviour in hens housed in groups. A population of 662 hens was genotyped for 1536 SNPs of which 1022 could be used for the association study. The analysis was conducted across 9 different lines of White Leghorn and Rhode Island Red origin. Across lines linkage disequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 42 publications
7
83
0
1
Order By: Relevance
“…However, if many loci influence the trait, dominance variance can be small, despite substantial 2 ), dominance variance will decrease when the number of loci increases and heterosis is constant (Robertson et al 1983;Falconer and Mackay 1996). Hence, this suggests that survival time is affected by many loci, which is consistent with results from Biscarini et al (2010), who found 11 direct QTL and 81 indirect QTL for feather score, which is a precursor of survival. Table 4 shows the estimated parameters, for purebreds, from the direct-indirect animal model.…”
Section: Purebred-crossbred Comparisonsupporting
confidence: 88%
See 1 more Smart Citation
“…However, if many loci influence the trait, dominance variance can be small, despite substantial 2 ), dominance variance will decrease when the number of loci increases and heterosis is constant (Robertson et al 1983;Falconer and Mackay 1996). Hence, this suggests that survival time is affected by many loci, which is consistent with results from Biscarini et al (2010), who found 11 direct QTL and 81 indirect QTL for feather score, which is a precursor of survival. Table 4 shows the estimated parameters, for purebreds, from the direct-indirect animal model.…”
Section: Purebred-crossbred Comparisonsupporting
confidence: 88%
“…These genes can reinforce differences between males and females as, despite a certain degree of dosage compensation, certain parts of the chromosome remain unequally expressed in males and females (Xu et al 2002;Arnold et al 2008). Biscarini et al (2010) found evidence for Z chromosome linked IGEs in an association study on feather condition score in laying hens. Feather condition score serves as a measure for the severity of feather pecking.…”
Section: Genetic Parameters Between Crossesmentioning
confidence: 98%
“…Like mammals, TIM families in avian species seem to be diverse, with TIM1, TIM3 and TIM4 in a wild bird (zebrafinch) but only TIM1 and TIM4 in the domestic birds (turkey and chicken). Chromosome 13 regions have been linked to genetic control of innate and acquired immunity in layer birds 43. It would be of some interest to determine if there is within‐species variation in TIM1 and TIM4 expression levels that could contribute to immune phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Keeling et al (2004) showed that a QTL for feather damage in chickens coincided with the dominant white pigmentation locus. Biscarini et al (2010) carried out a genome-wide association study and detected different chromosomal regions involved in feather damage in hens.…”
Section: Genetics Of the Behavioural Response To Changes In The Sociamentioning
confidence: 99%
“…This approach, which enables integration of both the animal's performance and its influence on that of other group members in the genetic evaluation, is attractive because it promotes sociality indirectly. Biscarini et al (2010) showed the advantages of a social genetic model used to select against feather pecking in hens. A better understanding of the molecular mechanisms of action of the genes located on GGA1 (which have a strong effect on growth and a wide array of pleiotropic effects on welfare traits) may precede marker-assisted selection (Wiré n and Jensen, 2010).…”
Section: Maternal Behaviourmentioning
confidence: 99%